(untitled) (Eureka Journal of Agricultural Science & Bio-Innovation, 2026)
The objective of this research was to refine open-field cultivation technologies for sweet peppers by enhancing yield through the application of foliar-based growth regulators. The study was conducted between 2022 and 2024 under the agro-climatic conditions of the Tashkent region. Experiments utilized the following sweet pepper hybrids: Gemini F1, Abadiya F1, and Nargiza F1. The methodology integrated a drip irrigation system with the application of growth-stimulating preparations, specifically T-86 and Bist, at concentrations of 1.0 ml and 1.5 ml per liter of water. The treatment protocol involved three successive applications of the working solution, administered via foliar spraying at a rate of 1 L per 30 m2.